2010
DOI: 10.1007/s10800-010-0197-4
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of dehumidifying performance of solid polymer electrolytic dehumidifier for practical application

Abstract: A two-layer model for a solid polymer electrolytic (SPE) dehumidifier is applied to a system in which the chamber to be dehumidified has some leakage area. By introducing this area, the attainable humidity in the chamber, which is the steady-state humidity to be attained after a long-time dehumidification, can be defined. Experimental results of dehumidification by an SPE dehumidifier are compared to the calculations based on the two-layer model for the SPE dehumidifier, which was presented in our previous pap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 6 publications
0
5
0
Order By: Relevance
“…Our device showed better humidity transfer performance when compared to TE cooling and solid polymer electrolyte membrane dehumidifiers, [19][20][21][22] reported in the literature (Figure 3F). Note that, we recalculated the experimental results reported in these references according to the same assessment criteria.…”
Section: Humidity Pump Characteristicsmentioning
confidence: 48%
“…Our device showed better humidity transfer performance when compared to TE cooling and solid polymer electrolyte membrane dehumidifiers, [19][20][21][22] reported in the literature (Figure 3F). Note that, we recalculated the experimental results reported in these references according to the same assessment criteria.…”
Section: Humidity Pump Characteristicsmentioning
confidence: 48%
“…Therefore, the current under a steadystate condition should be proportional to the supply rate of water to the anode area. The authors showed the relation between the steady-state current of the dehumidifying element and the water content in the vicinity of the electrodes in a previous article [2], as follows.…”
Section: Consideration Of the Steady-state Current And Effect Of The mentioning
confidence: 99%
“…On the other hand, the current of the SPE dehumidifying element was found to be proportional to the water content in the vicinity of the anode, and the following formula was presented in our previous article [1,2], when the applied voltage is constant.…”
Section: Consideration Of the Steady-state Current And Effect Of The mentioning
confidence: 99%
See 1 more Smart Citation
“…An alternative technology that has attracted increasing interest in the past few years is ionic membranes [20][21][22][23][24][25][26][27]. These devices work based on electrolysis, and they typically comprise a proton-conductive electrolytic layer sandwiched between two porous electrodes with catalytic layers composed of noble metal particles.…”
Section: Introductionmentioning
confidence: 99%